Pillar depicting image of four-armed Parvati - Temples of India Project Team (Jio Institute, 2024)
The pillars in the mandapa of the Harshnath temple lack homogeneity and may have been a later replacement. One of these pillars is adorned with intricate carvings of apsaras and female deities like Parvati, as seen in this image, within the niches of the pillar. Beneath these pillar niches are panels depicting musicians, dancers, celestial beings, deities like Ganesha and ascetics. The four-armed Goddess, likely Parvati, seems to be standing on a vahana resembling an iguana. Two attributes certainly identifiable are a mala and a flower. The panel below depicts two figures engaged in a discussion, over a text.